2018
DOI: 10.3345/kjp.2018.61.2.59
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac function associated with home ventilator care in Duchenne muscular dystrophy

Abstract: PurposeCardiomyopathy is becoming the leading cause of death in patients with Duchenne muscular dystrophy because mechanically assisted lung ventilation and assisted coughing have helped resolve respiratory complications. To clarify cardiopulmonary function, we compared cardiac function between the home ventilator-assisted and non-ventilator-assisted groups.MethodsWe retrospectively reviewed patients with Duchenne muscular dystrophy from January 2010 to March 2016 at Gangnam Severance Hospital. Demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Literature review (Online Table 5.4) Due to ethical constraints, the benefits on NIV have not been confirmed in randomized controlled trials and the published cohort studies mainly consist of a limited number of patients. NIV is associated with: o an increase in survival in patients with SMA type 1 [57,62,65,66,209] and Duchenne muscular dystrophy [71,210] o fewer hospitalizations in patients with SMA type 1 [57,61,62,64,209], and some NMD [211,212]); but no change in hospitalizations in other children with NMD [213] o improvement in SDB symptoms in patients with SMA type 2-3 [60], infantile Pompe disease [73], and other NMD [69,82,84] o improvement in nocturnal and daytime gas exchange in patients with juvenile Pompe disease [72], and NMD [82] o improvement in sleep quality/architecture and cyclic-alternating patterns in patients with SMA type 1-2 [60], SMA type 2 [214], and other NMD [69,82] o decrease in chest deformity in patients with SMA type 1 [58,63], and SMA type 1-3 [61] o transient improvement in predicted FVC and thoraco-abdominal asynchrony in patients with Duchenne muscular dystrophy [215] o improvement in cardiac function in patients with Duchenne muscular dystrophy [216] o improvement in QoL in children with NMD [217].…”
Section: Benefits Of Nivmentioning
confidence: 99%
“…Literature review (Online Table 5.4) Due to ethical constraints, the benefits on NIV have not been confirmed in randomized controlled trials and the published cohort studies mainly consist of a limited number of patients. NIV is associated with: o an increase in survival in patients with SMA type 1 [57,62,65,66,209] and Duchenne muscular dystrophy [71,210] o fewer hospitalizations in patients with SMA type 1 [57,61,62,64,209], and some NMD [211,212]); but no change in hospitalizations in other children with NMD [213] o improvement in SDB symptoms in patients with SMA type 2-3 [60], infantile Pompe disease [73], and other NMD [69,82,84] o improvement in nocturnal and daytime gas exchange in patients with juvenile Pompe disease [72], and NMD [82] o improvement in sleep quality/architecture and cyclic-alternating patterns in patients with SMA type 1-2 [60], SMA type 2 [214], and other NMD [69,82] o decrease in chest deformity in patients with SMA type 1 [58,63], and SMA type 1-3 [61] o transient improvement in predicted FVC and thoraco-abdominal asynchrony in patients with Duchenne muscular dystrophy [215] o improvement in cardiac function in patients with Duchenne muscular dystrophy [216] o improvement in QoL in children with NMD [217].…”
Section: Benefits Of Nivmentioning
confidence: 99%
“…Twenty-seven boys and adolescent and young adult males (median age 15 years; range, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were included in the study. Most of the participants had 3 or 4 clinic visits (median, 3; range, 1-10).…”
Section: Resultsmentioning
confidence: 99%
“…Lee and colleagues demonstrated that optimizing ventilatory support with NIV decreases the LV afterload, leading to an improved diastolic function and likely to a slowing of the progression of dilated cardiomyopathy. The linear mixed model was adjusted for the duration of NIV.…”
Section: Methodsmentioning
confidence: 99%
“…Progression of cardiomyopathy is the major cause of mortality. Cardiomyopathy can occur at any age but often occurs around 14–15 years [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baseline assessment of cardiac function is needed for patients with DMD at diagnosis, and annual cardiac assessment is recommended for patients with DMD older than 10 years. Poor treatment outcomes have been noticed in patients with DMD who fail to see a cardiologist after the onset of clinical symptoms of heart failure [ 2 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%